Viscoelastic ordering in microfluidic devices: current knowledge, open questions and challenges - Francesco Del Giudice; Gaetano D’Avino (JPhys Materials)
Objects flowing in microfluidic devices can self-organise in ordered structures thanks to the hydrodynamic interactions mediated by either inertial or viscoelastic forces. Such structures have been found to be crucial to enhancing microfluidic applications such as single encapsulation, co-encapsulation, and material synthesis. However, while inertial ordering has been investigated in more detail, studies on viscoelastic ordering are much more limited. In this perspective, we report the recent advancements in viscoelastic ordering while also discussing the open questions and challenges related to this field. We also include a brief description of both experimental and numerical protocols that can be employed to investigate viscoelastic ordering.